Novel Dual Inhibitors of Nuclear Factor-Kappa B (NF-κ B) and Cyclooxygenase- 2 (COX-2): Synthesis, In Vitro Anticancer Activity and Stability Studies of Lantadene–Non Steroidal Anti-inflammatory Drug (NSAID) Conjugates - Kumar Suthar, Sharad; Sharma, Neetika; Boon Lee, Hong; Nongalleima, Khumukcham; Sharma, Manu (Current Topics in Medicinal Chemistry, 2014)
The activation of transcription factors nuclear factor-kappa B (NF-κ B) and cyclooxygenase-2 (COX-2) is critical in cancer; they act synergistically in promoting tumor growth, survival, and resistance to chemotherapy. Thus, combined targeting of NF-κ B and COX-2 present an opportunity for synergistic anticancer efficacy. The ester prodrugs of pentacyclic triterpenoids reduced lantadene A (3), B (4), and its congener 22β-hydroxyoleanonic acid (5) with various non steroidal anti-inflammatory drugs (NSAIDs) present a novel approach. The ester prodrugs of 3 and 4 with diclofenac showed promising dual inhibition of NF-κ B and COX-2. The lead prodrugs 14 and 15 exhibited inhibition of inhibitor of nuclear factor-kappa B kinaseβ (IKKβ ) in the single-digit micromolar range and at the same time, prodrugs 14 and 15 showed marked cytotoxicity against A549 lung cancer cell line with IC50s 0.15 and 0.42 μM, respectively. The prodrugs 14 and 15 exhibited stability in the acidic pH and were hydrolyzed readily in the human blood plasma to release the active parent moieties. Thus, we have synthesized novel hybrid compounds to target both NF-κ B and COX-2 via a prodrug approach, leading to promising anticancer candidates.
Keywords: lantadene-non steroidal anti-inflammatory drug conjugates